AKTIVITAS ANTIOKSIDAN DAN ANTIHIPERKOLESTEROLEMIA IN VITRO DARI CAMPURAN EKSTRAK ANGKAK DAN BEKATUL - Hasim -; Qomariah Hasanah; Dimas Andrianto; Didah Nur Faridah (Departemen Ilmu dan Teknologi Pangan, IPB Indonesia bekerjasama dengan PATPI, 2018)
Red yeast rice (RYR) and rice bran (RB) have been reported to have many biological activities, such as anticancer, antioxidant, antidiabetes and antihypercholesterolemia. This research aimed to determine the best fraction of RYR extract as a HMG CoA reductase inhibitor and the best ratio of the mixture of RYR and RB extract fraction as a HMG CoA reductase inhibitor and an antioxidant using in vitro assays. RYR and RB were individually extracted using ethanol 95%, followed by liquid-liquid fractionation using n-hexane, dichloromethane, etyhl acetate, and water. The RYR extract fraction with the best HMG CoA reductase inhibition was then mixed with RB extract in various ratios for HMG CoA reductase inhibition test and antioxidant activity by FRAP method, as well as analysis of total phenolics and flavonoids content. The results showed that the strongest inhibitory effect to the HMG CoA reductase was found in the water fraction of RYR extract (37.37%). The mixture of RYR and RB water extract fractions with a ratio of RYR:RB 1:3 had the strongest inhibition (51.85%) as compared to other ratios, followed by a ratio of 2:2 (51.03%) and 3:1 (42.36%). The best antioxidant activity was found in the RYR:RB ratio of 1:3 (24.76 mg TE/g). The highest total phenolic and flavonoid content was found in the RYR:RB ratio of 2:2 (11.17 mg GAE/g) and the RYR:RB ratio of 3:1 (7.44 mg QE/g). Overall, the addition of RB extract into the RYR extract was able to provide a significantly better HMG CoA reductase inhibitory effects and antioxidant acti-vity than RYR extract alone.